2015
DOI: 10.3389/fncir.2015.00049
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory thalamus: unanswered questions about the role of the mediodorsal thalamic nucleus in olfaction

Abstract: The mediodorsal thalamic nucleus (MDT) is a higher order thalamic nucleus and its role in cognition is increasingly well established. Interestingly, components of the MDT also have a somewhat unique sensory function as they link primary olfactory cortex to orbitofrontal associative cortex. In fact, anatomical evidence firmly demonstrates that the MDT receives direct input from primary olfactory areas including the piriform cortex and has dense reciprocal connections with the orbitofrontal cortex. The functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 88 publications
6
68
0
Order By: Relevance
“…Although olfactory processing has a nonobligatory thalamic relay (e.g., in contrast to vision), thalamic lesions cause impairments in odor functioning (29), i.e., in identification and in evaluation of pleasantness. Moreover, it has been suggested that thalamic nuclei receive indirect olfactory input from olfactory cortex (30). That odor pleasantness is associated with thalamic activity (31) is of further interest, given that in our data the pleasantness of the sick body odor was reduced compared with the control pad but was only insignificantly reduced compared with the healthy body odor.…”
Section: Discussionmentioning
confidence: 52%
“…Although olfactory processing has a nonobligatory thalamic relay (e.g., in contrast to vision), thalamic lesions cause impairments in odor functioning (29), i.e., in identification and in evaluation of pleasantness. Moreover, it has been suggested that thalamic nuclei receive indirect olfactory input from olfactory cortex (30). That odor pleasantness is associated with thalamic activity (31) is of further interest, given that in our data the pleasantness of the sick body odor was reduced compared with the control pad but was only insignificantly reduced compared with the healthy body odor.…”
Section: Discussionmentioning
confidence: 52%
“…Instead, olfactory cortical areas (piriform, orbitofrontal, and entorhinal cortices) are directly supplied by the olfactory bulb, while the mediodorsal thalamic nuclei function as higher order processing units in the olfactory system (Tham et al. ; Courtiol and Wilson ). ANO2 expression has not been demonstrated for these nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…However, a link between these neurons and the olfactory phenotype of Ano2 À/À mice is difficult to envisage, as olfaction is the one sensory modality that does not channel its afferent signals through primary thalamic nuclei toward the cortex. Instead, olfactory cortical areas (piriform, orbitofrontal, and entorhinal cortices) are directly supplied by the olfactory bulb, while the mediodorsal thalamic nuclei function as higher order processing units in the olfactory system (Tham et al 2009;Courtiol and Wilson 2015). ANO2 expression has not been demonstrated for these nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Based on its specific characteristics like the close anatomical connection to the limbic system, with only two synapses between the olfactory neuron and the amygdala (Herz, 2005) and a minor involvement of the thalamus in contrast to other sensory modalities (although recently a greater contribution of the medidorsal thalamic nucleus to olfaction is discussed, for review see Courtiol and Wilson, 2015), the olfactory systems and the processes related to it gain more and more interest. Furthermore, olfactory deficits are known to be present in neurological diseases such as Alzheimer's and Parkinson's disease (Doty et al, 2015;Landis et al, 2005) and psychiatric disorders like Schizophrenia and post-traumatic stress disorder (PTSD, Doty et al, 2015;Vasterling et al, 2000) and therefore represent an important field of olfaction research.…”
Section: Conclusion and Limitationsmentioning
confidence: 98%